Privatization of Public Space: Spatial Practice in the Umbrella Movement. Issue 4 (November 2019) - Tang, Kin-Ling
This article argues that in order to understand the resistance potentials of taking space movements, the temporal dimensions and spatial practices implied cannot be neglected, or else there would be a tendency to be overoptimistic about resistance in these movements. Using the Umbrella Movement that took place in Hong Kong in 2014 as a case study, this article notes that representational space and spatial practice by protesters were guided by a dualistic view of the public and the private, which in turn is the dominant ideology in neoliberalism, and that their acts of resistance were not able to go beyond the confines of conceived space. In the movement, protesters reclaimed public spaces through privatizing them. Based on the work of Lefebvre, this article argues that only with a radical critique of neoliberal values embedded in capitalism including the public-private dualism can any real transformations of everyday life and hence revolution be possible.